Aerodynamics of bicycle helmets - Alam, F.; Subic, A.; Akbarzadeh, A. (The Engineering of sport 7, Volume 1, 2008)
The aerodynamic efficiency is an important design criterion for bicycle helmets. The characteristics of venting geometry, venting orientation and venting location play a vital role in aerodynamic drag. In order to design an aerodynamically efficient bicycle helmets, a comprehensive study is required. Therefore, the primary objectives of this work were to study the aerodynamic efficiency as a function of venting geometry, venting location and orientation for a series of recreational production helmets currently available in Australian market.